Survey and Seasonal Abundance of the Predutors of the Ceroplasts Rusci L. (Homopteru coccidae) in Al-Beida Region, Libya - Abdulhamid, Abdulhamid (Al-Mukhtar Journal of Sciences, 2006)
In the present study ten predator species were recorded on the fig wax scale, Ceroplastes rusci L. at El-Baida region, Libya, including two species for each of families, Coccinellidae, Anthocoridae and Chrysopidae, one species for each of families, Phloeothripidae, Noctuidae and Mantidae.The species, Orius albidipennis, Chrysoperla carnea, Mallada sp. and Sphex sp., occurred for long periods, which ranged between 18 – 24 weeks.The obtained data revealed that eight species namely, Scymnus syriacus. O. albidipennis, Anthocoris sp., C. carnea, Mallada sp., Haplothrips sp., Sphex sp. and Iris oratorial a new  predators for C. rusci in El-Beida region.